Pertimbangan Hukum Putusan Bebas Pada Perkara Tindak Pidana Korupsi (Studi Kasus Pada Perkara Nomor: 19/Pid.TPK/2021/PN.SMG) - David Bani Adam (Kosmik Hukum, 2022)
The purpose of writing this article is to find out how the legal considerations of judges' decisions in cases of corruption are acquitted (vrijspraak) Case number: 19/Pid.TPK/2021/PN.SMG based on the Criminal Procedure Code. The method in this study uses a normative legal research method using a law approach. concluded1. The types of judge's decisions in cases of criminal acts of corruption based on the Criminal Procedure Code are free and free from all lawsuits or criminal charges. The judge's verdict is free if it is not proven legally and convincingly that the defendant is guilty of committing the crime charged. The sentencing decision is handed down if the judge is of the opinion that the defendant is legally and convincingly proven guilty of committing the crime for which he is charged. 2. Legal considerations of the panel of judges in passing an acquittal against the crime of corruption number: 19/Pid. TPK / 2021 / PN. SMG). The author concludes that the court's decision on the criminal act of corruption that acquits the defendant is basically permissible. As long as the judge's decision has the essence of a strong and accountable rati legis, on the basis of considerations of the value of justice and considerations of judex factie as in the a quo case.Keywords: Legal Considerations, Free Decisions, Corruption Crimes